2023
DOI: 10.48550/arxiv.2302.06660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMEFiT: a flexible toolbox for global interpretations of particle physics data with effective field theories

Abstract: The Standard Model Effective Field Theory (SMEFT) provides a robust framework to interpret experimental measurements in the context of new physics scenarios while minimising assumptions on the nature of the underlying UV-complete theory. We present the Python open source SMEFiT framework, designed to carry out parameter inference in the SMEFT within a global analysis of particle physics data. SMEFiT is suitable for inference problems involving a large number of EFT degrees of freedom, without restrictions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In our analysis, we aim to leverage the detector-simulation capabilities of the MadAnalysis 5 and Rivet frameworks (including our implementation of HEPTopTagger) to realistically explore the effects of effective operators on the reconstruction performance of boosted top quarks. Among the full set of potentially impactful SMEFT operators [39], only eight of them are not too strongly constrained by other means [40][41][42][43][44][45], so that an investigation of pair-production and decay of boosted top quarks could offer new handles on them. They read, in the notation of Ref.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, we aim to leverage the detector-simulation capabilities of the MadAnalysis 5 and Rivet frameworks (including our implementation of HEPTopTagger) to realistically explore the effects of effective operators on the reconstruction performance of boosted top quarks. Among the full set of potentially impactful SMEFT operators [39], only eight of them are not too strongly constrained by other means [40][41][42][43][44][45], so that an investigation of pair-production and decay of boosted top quarks could offer new handles on them. They read, in the notation of Ref.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Global SMEFT interpretations of measurements at the LHC in the top sector have recently been achieved by several groups [40][41][42][43][44][45]. These studies demonstrated in particular that dozens of SMEFT operators could be constrained (and therefore determined) simultaneously, correlating sometimes information originating from different sectors.…”
Section: Introductionmentioning
confidence: 99%